Youths' preference towards hiking trail selection in Bukit Keluang, Terengganu, Malaysia - Abdul Aziz, Nor Akmar; Mohamed Mokhtar, Mohamed Daniel; Nasir, Rabiatul Adawiyah; Mohd Sidi, M Adli; Mohamed Mokhtar, Mohamed Daniel; Abd Rahaman, Nur Faqihah (Jabatan Perhutanan Semenanjung Malaysia, 2024)
: This study investigated the factors influencing the decision-making of youth hikers regarding the trail preference between uphill and downhill routes in Bukit Keluang, Terengganu, Malaysia. Specifically, this study provides an understanding of how the aesthetics and conditions of trails affect hikers’ satisfaction which is crucial for effective trail management. We administered a questionnaire via Google Forms to 150 random respondents who had previously hiked in Bukit Keluang. The results indicated that the ease of the trail (64.7%), moderate steepness (51.3%), and the presence of ropes (44.7%) were the primary factors that influenced trail choice. Interestingly, exposed roots on the trails emerged as a significant preference factor, allowing hikers to move faster uphill and downhill. These findings highlight the importance of considering trail conditions and aesthetics when managing hiking destinations. The study provides valuable insights for trail management in Bukit Keluang, suggesting improvements in trail’s ease, steepness, and the provision of aids like ropes while highlighting the unexpected benefits of exposed roots. Overall, understanding young hikers’ preferences and satisfaction regarding the trail’s condition can aid in developing trail management strategies to enhance the hiking experience in Bukit Keluang.